Pengembangan Aplikasi Pendatan Aset BUMDes untuk meningkatkan Pelayanan Masyarakat Desa Binor Berbasis Framework Django - Ja'far Shudiq, Wali; Rizqiyah, Shofiatur; Saskiya Iskandar, Nur Aida; Sari, Intan Purnama (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2024)
Leasing is an important component in starting a business. Each village has a business entity called Village-Owned Enterprises (BUMDes). This business entity has one work program, namely renting BUMDes assets consisting of market stalls, tractors and weighing scales. Like the current rental process, you need to contact the BUMDes officer or go to the village office to find out the stock of goods and register. With limited access to tenant information, it is difficult to find out stock of goods, and for officers recording tenant data manually is also inefficient. Currently, almost all activities can be done online just by using internet facilities, which can make work easier, whether using websites or cellphone applications. To achieve the expected goals, researchers used a system development model, namely using a waterfall. This model is used for conceptualization at each stage so that the system development procedures that will be created later become clearer. For system design using Flowcharts, DFD, and ERD. By using the Django Web Framework which contains registration and rental of BUMDes assets carried out by tenants online so it is faster and more efficient. Therefore, the results of the creation system will make it easier to register and rent BUMDes assets and also make it easier for BUMDes officers to record tenant data.